SELECTION OF EXTRACTION TECHNOLOGY FOR GREEN TEA, COFFEE BEANS, IVAN-TEA - N. V. Makarova; D. F. Ignatova; N. B. Eremeeva (Современная наука и инновации, 2022)
Search of food, sposobstvuyuschih to reduce the risk of developing cancer - one of the important areas of the food industry.